2014
DOI: 10.1002/cctc.201402131
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation of Molecular Oxygen by an Iron(III) Porphyrin with a Magnesium Aluminum Layered Double Hydroxide for the Aerobic Epoxidation of Cyclohexene

Abstract: The photocatalytic aerobic epoxidation of cyclohexene proceeded under visible‐light irradiation only if 5,10,15,20tetrakis(pentafluorophenyl)porphyrin iron(III) chloride ([FeIII(TPFPP)Cl]) was combined with Mg‐Al layered double hydroxide (Mg‐Al LDH) as a solid base in chloroform. The OH groups in the Mg‐Al LDH exchanged with the axial Cl ligands in [FeIII(TPFPP)Cl] to afford [FeIII(TPFPP)OH], which functioned photocatalytically in the presence of Mg‐Al LDH but was inactive in its absence. The band in the actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The catalyst was selective for 1,2-epoxycyclohexane during photocatalytic aerobic cyclohexene epoxidation. The authors concluded that [Fe(TPFPP)Cl]/Mg/Al-LDH was an effective photocatalyst for the oxidation of various alkenes [58].…”
Section: Ldh and Lhs As Support For Metalloporphyrin Immobilizationmentioning
confidence: 99%
“…The catalyst was selective for 1,2-epoxycyclohexane during photocatalytic aerobic cyclohexene epoxidation. The authors concluded that [Fe(TPFPP)Cl]/Mg/Al-LDH was an effective photocatalyst for the oxidation of various alkenes [58].…”
Section: Ldh and Lhs As Support For Metalloporphyrin Immobilizationmentioning
confidence: 99%
“…Using molecular oxygen as an oxidant is a longstanding strategic subject, and significant achievements in aerobic epoxidation have been made. Nevertheless, most reports have used metallic compounds/additives or metallic catalysts/coreductants (such as Et 2 Zn/amino alcohol, Co­(II)­TPP-OCH 3 /isobutyraldehyde, and Mn­(TPP)­OAc/isobutyraldehyde) (Scheme a), which always lead to metal residue and poor atom economy. Only a limited number of reports , related to the catalytic epoxidation of α,β-unsaturated ketones with molecular oxygen as the oxidant in the absence of metallic compounds have been reported.…”
Section: Introductionmentioning
confidence: 99%